Pengelompokkan Tingkat Pemahaman Guru PAUD Terhadap Pembelajaran Berbasis STEAM Menggunakan Metode X-Means Clustering - Siti Fatimah; Suriati Suriati; Ari Usman (Explorer, 2022)
In the era of the industrial revolution 4.0, quantity is not a measure of achieving early childhood outcomes, but how teachers create quality resource based inventions. To form creative and adaptive resources for technology, the teacher must changes the facilities, infrastructure and learning reconstruction. Learning that is prepared to welcome children to face the 21st century is learning based on Science, Technology, Engineering, Art, and Mathematics (STEAM). STEAM is used to consider the interconnected essence of science, technology, engineering, arts and mathematics disciplines and their significance in the long-term academic performance of children. Responding to STEAM-based learning that PAUD teachers need to incorporate in cultivating the creativity of children, it is important to know the degree to which PAUD teachers understand STEAM-based learning. This research discusses the use of the X-Means clustering algorithm as one of the data mining algorithms in grouping data on the level of comprehensions of PAUD teachers on STEAM-based learning. This research discusses the use of the X-Means Clustering algorithm as one of the data mining algorithms in grouping data on the level of comprehensions of PAUD teachers on STEAM-based learning.